Modeling financial markets : using visual basic NET and Databases to Create pricing, trading and risk Management Models - Benjamin Van Vliet (McGraw Hill, 2004)
File program dalam bentuk Excel, Word, dll; Isi: Appendix, ch3-ch20, Xtras, dll; Judul dalam kemasan.